Perbedaan Peningkatan Kemampuan Pemecahan Masalah Matematika Dengan Media Gambar Dan Autograph Menggunakan Model Pembelajaran CTL - Hutasuhut, Rita Nauli; Karnasih, Ida; Salayan, Madyunus (Edumaspul: Jurnal Pendidikan, 2020)
The purpose of this study is to determine whether there are differences in the improvement of mathematical problem solving abilities that obtain CTL learning through autograph software and image media.The research method used in this study is a quasi-experimental research method. The population referred to in this study were all students of class X IPA.1 and X.IPA 2 Al Washliyah High School 3 Medan Academic Year 2018/2019. The sample in this study was taken based on the study population consisting of two classes X, namely class X. IPA 1 and X. IPA 2, where class X. IPA 1 number of students was 20 people as first class of expedition with CTL learning using media Autograph and class X IPA 2: the number of students is 23 as the second expiry class with CTL learning using the Picture media. The instrument used to get the data of this study is tests and questionnaires. The results of this study indicate that there is an increase in mathematical problem solving abilities that accept the learning model Contextual Teaching Learning (CTL) through software autographs and media images, this is evidenced by the results of tcount for the ability to solve mathematical problem solving in experimental class I of 3.70 and experimental class II of 2.22. Keywords: CTL, Problem Solving, , Media Image, Autograph